Diabetes-linked transcription factor HNF4? regulates metabolism of endogenous methylarginines and ?-aminoisobutyric acid by controlling expression of alanine-glyoxylate aminotransferase 2 - Burdin, Dmitry V.; Kolobov, Alexey A.; Brocker, Chad; Soshnev, Alexey A.; Samusik, Nikolay; Demyanov, Anton V.; Brilloff, Silke; Jarzebska, Natalia; Martens-Lobenhoffer, Jens; Mieth, Maren; Maas, Renke; Bornstein, Stefan R.; et al. (Scientific Reports, 2016)
Elevated levels of circulating asymmetric and symmetric dimethylarginines (ADMA and SDMA) predict and potentially contribute to end organ damage in cardiovascular diseases. Alanine-glyoxylate aminotransferase 2 (AGXT2) regulates systemic levels of ADMA and SDMA, and also of beta-aminoisobutyric acid (BAIB)-a modulator of lipid metabolism. We identified a putative binding site for hepatic nuclear factor 4 ? (HNF4?) in AGXT2 promoter sequence. In a luciferase reporter assay we found a 75% decrease in activity of Agxt2 core promoter after disruption of the HNF4? binding site. Direct binding of HNF4? to Agxt2 promoter was confirmed by chromatin immunoprecipitation assay. siRNA-mediated knockdown of Hnf4a led to an almost 50% reduction in Agxt2 mRNA levels in Hepa 1-6 cells. Liver-specific Hnf4a knockout mice exhibited a 90% decrease in liver Agxt2 expression and activity, and elevated plasma levels of ADMA, SDMA and BAIB, compared to wild-type littermates. Thus we identified HNF4? as a major regulator of Agxt2 expression. Considering a strong association between human HNF4A polymorphisms and increased risk of type 2 diabetes our current findings suggest that downregulation of AGXT2 and subsequent impairment in metabolism of dimethylarginines and BAIB caused by HNF4? deficiency might contribute to development of cardiovascular complications in diabetic patients.
EVALuna2:8702